Temperature- and Time-Dependent Dielectric Measurements and Modelling on Curing of Polymer Composites - Prastiyanto, Dhidik (Karlsruher Forschungsberichte aus dem Institut für Hochleistungsimpuls- und Mikrowellentechnik, 2016)
In this book a test set for dielectric measurements at 2.45 GHz during curing of polymer composites is developed. Fast reconstruction is solved using a neural network algorithm. Modeling of the curing process at 2.45 GHz using both dielectric constant and dielectric loss factor results in more accurate model compared to low frequency modelling that only uses the loss factor. Effect of various hardeners and different amount of filler is investigated.